PENDAMPINGAN PEMANFAATAN GOOGLE SHEETS SEBAGAI MEDIA DIGITAL DALAM PENYUSUNAN LAPORAN KEUANGAN UMKM: Assistance in Utilizing Google Sheets as a Digital Tool for Preparing MSME Financial Reports - Dara Nida Utamie; Baiq Dewi Lita Andiana; Triana Lidona Aprilani; Sukriati Sukriati; Muhammad Habibullah Aminy; Fathurrahman Fathurrahman (Al-Amal: Jurnal Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs)play a strategic role in the economy; however, they continue to face various challenges in financial management, particularly in maintaining orderly and sustainable financial records and preparing financial statements. Low levels of accounting literacy, limited utilization of digital technology, and reliance on manual record- keeping remain the main problems encountered by MSME actors.  This community service activity aims to improve MSME actors’ understanding and skills in preparing simple digital- based financial statements through assistance in utilizing Google Sheets. The implementation methods include the stages of preparation, socialization, practice-based training, intensive mentoring, and evaluation. The results of the activity indicate an improvement in MSME actors’ ability to record transactions regularly, separate business and personal finances, and prepare simple  income  statements  and cash flow  statements  more  accurately  and  efficiently.  The utilization of Google Sheets has proven to be a practical, affordable, and easily accessible digital solution for MSMEs. Therefore, it is expected to encourage the sustainable adoption of digital financial record-keeping as a basis for business decision-making and enhancing the competitiveness of MSMEs